1995
DOI: 10.2214/ajr.164.1.7998575
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic localized dilatation of the ileum in adults: findings on barium studies.

Abstract: OBJECTIVE.Idiopathic localized dilatation of the ileum is a rare entity characterized by a sharply demarcated segmental dilatation of the small bowel that is in line with the and In one, the lesion was seen on a barium enema with reflux into the ileum. The mean age of patients was 52 years. In seven cases, pathologic correlation was available.In the other two patients, long-term clinical follow-up and repeat studies confirmed the diagnosis. Resected specimens showed a thin but otherwise normal wall with normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 3 publications
1
35
0
Order By: Relevance
“…5 Because mucosal ulceration is common with segmental dilation of the small bowel, anemia or abdominal pain in older children may be the presenting sign or symptom. 4 When such symptoms are present, surgical excision of the dilated segment is recommended as a cure for the condition.…”
Section: Discussionmentioning
confidence: 99%
“…5 Because mucosal ulceration is common with segmental dilation of the small bowel, anemia or abdominal pain in older children may be the presenting sign or symptom. 4 When such symptoms are present, surgical excision of the dilated segment is recommended as a cure for the condition.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, a barium study that shows isolated localized intestinal dilation helps to make the diagnosis. 8 There is disagreement about the pathogenesis of SID. Irving and Lister, in explaining a correlation between SID and omphalocele, suggested that temporary extrinsic compression and bowel entrapment could lead to SID.…”
Section: Discussionmentioning
confidence: 99%
“…1 Some authors have called SID a giant Meckel diverticulum because the two entities have several similar characteristics. 8 SID may contain heterotopic gastric or pancreatic tissue and is commonly located in the ileum, although any sites throughout the digestive tract may be involved. Furthermore, an apparent feeding vessel to SID originating from the mesentery resembles the vitelline vessel seen with the Meckel diverticulum.…”
Section: Discussionmentioning
confidence: 99%
“…Segmental dilatation of the ileum is an unusual condition, and a review of the literature revealed that a large proportion (45%) of all the reported patients (n=53) with segmental dilatation of ileum were neonates [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The rest were distributed among the infant and children (32%) and adult (23%) age groups.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been called idiopathic localized dilatation of the ileum, ileal dysgenesis, segmental mega-ileum, and giant Meckel's diverticulum [1]. The caliber of the bowel lumen increases locally without luminal obstruction or thickening of the bowel wall.…”
Section: Introductionmentioning
confidence: 99%